Neuropeptide-Induced Androgen Independence in Prostate Cancer Cells: Roles of Nonreceptor Tyrosine Kinases Etk/Bmx, Src, and Focal Adhesion Kinase - Lee, Li-Fen (American Society for Microbiology, 2001)
The bombesin/gastrin-releasing peptide (GRP) family of neuropeptides has been implicated in various in vitro and in vivo models of human malignancies including prostate cancers. It was previously shown that bombesin and/or neurotensin (NT) acts as a survival and migratory factor(s) for androgen-independent prostate cancers. However, a role in the transition from an androgen-dependent to -refractory state has not been addressed. In this study, we investigate the biological effects and signal pathways of bombesin and NT on LNCaP, a prostate cancer cell line which requires androgen for growth. We show that both neurotrophic factors can induce LNCaP growth in the absence of androgen. Concurrent transactivation of reporter genes driven by the prostate-specific antigen promoter or a promoter carrying an androgen-responsive element (ARE) indicate that growth stimulation is accompanied by androgen receptor (AR) activation. Furthermore, neurotrophic factor-induced gene activation was also present in PC3 cells transfected with the AR but not in the parental line which lacks the AR. Given that bombesin does not directly bind to the AR and is known to engage a G-protein-coupled receptor, we investigated downstream signaling events that could possibly interact with the AR pathway. We found that three nonreceptor tyrosine kinases, focal adhesion kinase (FAK), Src, and Etk/BMX play important parts in this process. Etk/Bmx activation requires FAK and Src and is critical for neurotrophic factor-induced growth, as LNCaP cells transfected with a dominant-negative Etk/BMX fail to respond to bombesin. Etk's activation requires FAK, Src, but not phosphatidylinositol 3-kinase. Likewise, bombesin-induced AR activation is inhibited by the dominant-negative mutant of either Src or FAK. Thus, in addition to defining a new G-protein pathway, this report makes the following points regarding prostate cancer. (i) Neurotrophic factors can activate the AR, thus circumventing the normal growth inhibition caused by androgen ablation. (ii) Tyrosine kinases are involved in neurotrophic factor-mediated AR activation and, as such, may serve as targets of future therapeutics, to be used in conjunction with current antihormone and antineuropeptide therapies.